Metaconsumption and the Bible - Armenteros, Víctor M. (2018)
The objective of this article is to find the definitions of the concepts related to metaconsumption, consumerism and hyperconsumption in the Old Testament texts, and New Testament proposals and solutions. The conclusion offers constructive encouragement regarding possible updates that generate perception and understanding of the myth regarding metaconsumption and the Bible